MENELAAH PERAN PARA KATEKIS DALAM SPIRITUALITAS PEWARTAAN DI PAROKI SANTA MARIA ASSUMPTA KEUSKUPAN AGUNG KUPANG - Ngongo, Maria Hendritha Lidya; Taslulu, Beata Kristina; Luruk, Maria Inarita (STIPAS Keuskupan Agung Kupang, 2023)
The Catholic Church teaches that all Christian believers who have received the sacrament of baptism are called to carry out their responsibilities to be priests, prophets and kings. Lay people who are given a special task by the Church in the field of preaching the faith are called Catechists. Catechists should have a certain spirituality or enthusiasm for life to support their existence and ministry duties, especially in carrying out the five tasks of the Church. The aim of this research is to determine the role of catechists in church life, especially in the field of preaching. The method used is qualitative with a descriptive approach. The results of the research show that some catechists in the Santa Maria Assumpta Parish, Kupang Archdiocese have not taken an active part in carrying out their roles. Therefore, several activities are needed that can raise awareness within themselves so that catechists can involve themselves fully and actively in every ecclesiastical activity, especially assisting categorical groups in the Parish area in the field of preaching or catechesis.